PENGARUH KEPUASAN KERJA TERHADAP KINERJA GURU SMP NEGERI SEKECAMATAN MEUREUBO KABUPATEN ACEH BARAT STUDI KASUS UNTUK GURU YANG SUDAH MENERIMA TUNJANGAN SERTIFIKASI - Damrus Damrus (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2017)
Abstract  Teachers’ performance determines the quality of educational system. Education will be qualified when teachers are referred to the organized vision, mission, purpose, and goal in order to respond to various changes by generating all potential resources in educational institution. Teachers’ work satisfaction is one of the important aspects which have to be heeded by management in order to increase teachers’ quality of performance. When work satisfaction is fulfilled, teachers will tend to have high morale in doing their job. The objective of this research was to find out and to analyze the influence of certification allowance, work satisfaction and its effect on teachers’ performance at public junior high schools in Meureubo Subdistrict, West Aceh Regency. Work satisfaction had positive and significant influence on teachers’ performance at public junior high schools in Meureubo Subdistrict, West Aceh Regency. Keywords: Work Satisfaction, Certification Allowance, Teachers’ Performance